2006
DOI: 10.1380/ejssnt.2006.239
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular-dynamics simulations of thermal transport in carbon nanotubes with structural defects

Abstract: Effects of structural defects on thermal transport in carbon nanotubes are revealed through nonequilibrium molecular-dynamics simulations with the Tersoff-Brenner bond-order potential. The thermal conductivity of carbon nanotubes decreases rapidly down to 25 % with only 1 % vacancy defects. By performing thermal annealing, the vacancy defects are mainly transformed into 5-6 defects consisting of pentagon-hexagon pairs, and the reduced thermal conductivity due to vacancy defects is increased by 4-7 %. This impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 29 publications
5
30
0
Order By: Relevance
“…, where Λprist and Λdef are the MFPs in the pristine CNT and induced by defects. Assuming that cph and vg are independent on σ and Λdef is proportional to σ -β , we can obtain the fitting equation, [31], where α and β are fitting parameters. Solid (broken) lines in Fig.…”
Section: B Thermal Conductivity Of Defective Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…, where Λprist and Λdef are the MFPs in the pristine CNT and induced by defects. Assuming that cph and vg are independent on σ and Λdef is proportional to σ -β , we can obtain the fitting equation, [31], where α and β are fitting parameters. Solid (broken) lines in Fig.…”
Section: B Thermal Conductivity Of Defective Cntsmentioning
confidence: 99%
“…While the introduction of defects to CNTs, in general, reduces both electrical and thermal conductivity (or conductance), previous works have shown that the electrical and thermal properties have different sensitivity to the type of defect; the extent of reduction varies with the defect types for electrical conductivity [25][26][27][28] but varies less for thermal conductivity [29][30][31]. Note that most of the works so far on the effect of crystal disorder such as defects and strain on the electronic transport properties have been done for metallic CNTs [25][26][27][28]32,33], and there are only a few works on semiconducting CNTs, which dominantly contribute to the thermoelectric performance of CNT sheets.…”
Section: Introductionmentioning
confidence: 99%
“…vacancy defects, isotopes and Stone-Wales defects) reduce the phonon-derived thermal conductivity in CNTs [6,7]. Among these defects, a vacancy defect with three dangling bonds (hereinafter monovacancy) decreases the thermal conductivity most markedly [7]. Monovacancies are generated during the synthesis process or by artificial procedures such as acid purification and ion/electron irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is known that the atomic vacancy shown in Fig. 1 is not the most stable, [31][32][33][34] this defect is useful for clarifying the effect of defect on physical properties. [13][14][15][16][17][18] We can see two conductance dips: a broad dip around e F ¼ À0.25 eV and a sharp dip around e F ¼ 0.05 eV.…”
Section: A Single Atomic Vacancymentioning
confidence: 99%
“…This defect is composed of two pentagons and two hexagons: hereafter it is called 5-6 defect. 31,32 Figure 2(c) shows the Fermi-level dependence of the DC conductance. It has two dips at e F ¼ À0.7 eV and 0.6 eV due to the electron scattering by the defect states shown in Figs.…”
Section: B 5-6 Defectmentioning
confidence: 99%